Simple Transaction Models, Information and Computing - Stone, Richard (Review of Economic Studies, 1951)
Journal Article Simple Transaction Models, Information and Computing Get access Richard Stone Richard Stone Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 2, 1951, Pages 67–84, https://doi.org/10.2307/2295735 Published: 01 July 1951